Memahami Gerakan Perempuan Islam - Pasalli, Srijoni (Perspektif, 2011)
This article describes the movements of Islamic women. The movements show that a lot of women are discriminated against and have to undergo exploitations and violence on their basic rights. Muslim women's movements and/or the movements of Islamic feminism are the ongoing struggles to free them from the subordinate predetermination towards a more balanced and equal position in the society with men. Our questions then: "Are the movements purely Islamic ones? How can we comprehend the development of these movements in Indonesian context?"